Enzymatic recycling of ascorbic acid from dehydroascorbic acid by glutathione‐like peptides in the extracellular loops of aminergic G‐protein coupled receptors. Issue 7 (8th January 2016) - Root‐Bernstein, Robert; Fewins, Jenna; Rhinesmith, Tyler; Koch, Ariana; Dillon, Patrick F.
Abstract : The intracellular recycling of ascorbic acid from dehydroascorbic acid by the glutathione–glutathione reductase system has been well‐characterized. We propose that extracellular recycling of ascorbic acid is performed in a similar manner by cysteine‐rich, glutathione‐like regions of the first and second extracellular loops of some aminergic receptors including adrenergic, histaminergic, and dopaminergic receptors. Previous research in our laboratory demonstrated that ascorbic acid binds to these receptors at a site on their first or second extracellular loops, significantly enhancing ligand activity, and apparently recycling hundreds of times their own concentration of ascorbate in an enzymatic fashion. In this study, we have synthesized 25 peptides from the first and second extracellular loops of aminergic and insulin receptors and compared them directly to glutathione for their ability to prevent the oxidation of ascorbate and to regenerate ascorbate from dehydroascorbic acid. Peptide sequences that mimic glutathione in containing a cysteine and a glutamic acid‐like amino acid also mimic glutathione activity in effects and in kinetics. Some (but not all) peptide sequences that contain one or more methionines instead of cysteine can significantly retard the oxidation of ascorbic acid but do not recycle it from dehydroascorbate into ascorbate. Peptides lacking both cysteines and methionines uniformly failed to alter significantly ascorbate or dehydroascorbate oxidation or reduction. We believe that this is the first proof that receptors may carry out both ligand binding and enzymatic activity extracellularly. Our results suggest the existence of a previously unknown extracellular system for recycling ascorbate. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Ascorbic acid (vitamin C) binds to aminergic receptors enhancing their activity. Twenty‐five peptides from the extracellular loops of aminergic receptors were synthesized and compared directly with glutathione for their ability to prevent the oxidation of ascorbate and to regenerate ascorbate from dehydroascorbic acid. Extracellular recycling of ascorbate is comparable with the intracellular glutathione system and carried out by some cysteine‐rich, glutathione‐like regions of the first and second extracellular loops of adrenergic, histaminergic, and dopaminergic, but not insulin, receptors.